The Islamic Educational Curriculum and its Development in Islamic Schools in the Kurdistan Region of Iraq : Study and analysis - Hamadameen, Idrees Qadir; Mohammed , Taher Sheikh (Zanco Journal of Human Sciences, 2021)
The educational curriculum is the essential part of each educational system. This research deals with the Islamic educational curriculum, where it is taught in the official Islamic schools affiliated to the Ministry of Education in the Kurdistan Region of Iraq, and searches for the prevailing curriculum in informal Islamic mosque schools. The official Islamic schools that previously belonged to the Ministry of Endowment Religious affairs in the region had a specific approach as it has been mentioned through this research, then by a ministerial order the schools were transferred to the Ministry of Education, and then they modified the curricula of those schools and their development by several committees that had been formed from the ministries of education and higher education and scientific research and other experts with scientific specializations in the field. After a solid consideration, the research came to conclusion that the curriculum needs follow-up and some changes in its components for the cause of the constant change in the world and keeping pace with it. And so, it paves the way for the students who graduate from these schools to keep pace with changes and developments in the world.